2021
DOI: 10.3390/s21103549
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Assisted Living: A Review of Technologies, Methodologies and Future Perspectives for Healthy Aging of Population

Abstract: Over the last decade, there has been considerable and increasing interest in the development of Active and Assisted Living (AAL) systems to support independent living. The demographic change towards an aging population has introduced new challenges to today’s society from both an economic and societal standpoint. AAL can provide an arrary of solutions for improving the quality of life of individuals, for allowing people to live healthier and independently for longer, for helping people with disabilities, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 120 publications
0
62
0
Order By: Relevance
“…Cicirelli et al [3] identified the four main steps in developing an AAL system: sensor selection, data acquisition, recognition of elementary actions, and evaluations of complex behaviors. We also observe that most AAL solutions include sensing, transmitting, storing, and using data.…”
Section: Discussionmentioning
confidence: 99%
“…Cicirelli et al [3] identified the four main steps in developing an AAL system: sensor selection, data acquisition, recognition of elementary actions, and evaluations of complex behaviors. We also observe that most AAL solutions include sensing, transmitting, storing, and using data.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people face various diseases that need permanent healthcare systems and an accurate localization system to locate elderly people at the accident time. In [104], a comprehensive study is provided of the research and skills related to Active and Assisted Living (AAL) systems. The authors in [105] evaluate the widespread LoRaWAN communication infrastructure to alert a remotely connected healthcare server about elderly people accidents able to monitor the position and motion type of the elderly.…”
Section: Localization Methods In Smart Healthcarementioning
confidence: 99%
“… 2) studies that partially overlap with our studies, such as the literature review on PD diagnosis by Mei et al (2021) , that in addition to PD diagnosis by gait, also discuss other modalities such as voice, handwriting, magnetic resonance imaging (MRI), etc. 3) studies that are in the scope of this review but only cover a specific topic such as human motion trajectory prediction ( Rudenko et al, 2020 ), wearable sensing technologies for sports biomechanics ( Taborri et al, 2020 ), self-powered sensors and systems ( Wu et al, 2020 ), person re-Identification ( Wang et al, 2016 ), ( Nambiar et al, 2019 ), ( Karanam et al, 2019 ), machine learning in soft robotics ( Kim et al, 2021 ), ambient assisted living technologies (mostly AI-enabled and gait-related) ( Cicirelli et al, 2021 ), human action recognition ( Gurbuz and Amin, 2019 ), biomechanics ( Halilaj et al, 2018 ), gait recognition ( Kusakunniran, 2020 ), ( Singh et al, 2018 ), ( Wan C. et al, 2018 ), gait event detection and gait phase recognition ( Prasanth et al, 2021 ), clinical gait diagnostics of knee osteoarthritis ( Parisi et al, 2020 ), knee pathology assessment ( Abid et al, 2019 ), data preprocessing in gait classification ( Burdack et al, 2019 ), age estimation ( Aderinola et al, 2021 ), and banchamrk datasets ( Nunes et al, 2019 ). A survey paper by Alzubaidi et al (2021) provides an overview of deep learning, with helpful definitions and a discussion of strengths, limitations, and future trends of various deep learning techniques.…”
Section: Introductionmentioning
confidence: 99%